Реформування Збройних Сил України за стандартами НАТО - Романенко, Євген Олександрович (My University, 2016)
У статті наведено критичний аналіз розкриття змісту процесу реформування Збройних Сил України за стандартами НАТО. На основі існуючих підходів науковців, а також обґрунтованих нових наукових характеристик сформовано бачення реформування збройних сил за стандартами НАТО, яке прискорить створення справді професійної армії в Україні. The article provides a critical analysis of the disclosure of the content of the process of reforming the Armed Forces of Ukraine according to NATO standards. Based on existing approaches of scientists, as well as substantiated new scientific characteristics, a vision of reforming the armed forces according to NATO standards has been formed, which will accelerate the creation of a truly professional army in Ukraine.
Keywords: Збройні Сили України; Armed Forces of Ukraine; реформування; reformation; стандарти НАТО; NATO standards